OPTIMAL PRETREATMENT CONDITIONS OF INDUSTRIAL HEMP RESIDUES TO GLUCOSE - Blyahovski, Vencislav; Petrin, Stoyko; Valchev, Ivo; Toteva, Vesislava (Innovation in Woodworking Industry and Engineering design, 2025)
Hemp (Cannabis sativa L.) is an annual herbaceous plant with excellent agrarian and economic characteristics and has been used since ancient times as a raw material for making fabrics. Industrial hemp, with its high biomass yield per hectare, has great potential for the production of biofuels and valuable products. Regulatory documents in Bulgaria allow the cultivation of cannabis plants only if they are intended for fibres, seeds for animal feed or sowing if they have a content of less than 0.2% tetrahydrocannabinol. The residue of hemp after such processing is characterised by a hardwood-like content of cellulose, hemicellulose and lignin but with a very low bulk density. The specificity of the biomass residues and the woody structure of hemp stalks requires an additional mild, wet beating prior to enzymatic hydrolysis. The present work aims to investigate the effect of mechanical treatment of steam-exploded hemp residues on glucose yield after enzymatic hydrolysis and to determine the optimal pretreatment conditions. The classic steam and CO2 steam explosion methods are used as the first pretreatment step in this investigation. It has been found that the mechanical processing of hemp pulp leads to higher glucose yields after enzymatic hydrolysis, and this effect is reduced by increasing the steam explosion temperature.